2015
DOI: 10.1016/j.cmet.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Fine-Tunes Immune Homeostasis in Atherosclerosis and Colitis through Repression of Interleukin-10 Production

Abstract: Indoleamine 2,3-dioxygenase 1 (Ido1) is a rate-limiting enzyme that catalizes the degradation of tryptophan along the kynurenine pathway. Here, we show that Ido1 activity sustains an immunostimulatory potential through inhibition of interleukin (Il)10. In atherosclerosis, Ido1-dependent inhibition of Il10 translates into disease exacerbation. The resistance of Ido1-deficient mice to enhanced immune activation is broken in Ido1/Il10 double-deficient mice, which show exaggerated immune responses and develop seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 54 publications
0
107
1
Order By: Relevance
“…68,69 In experimental atherosclerosis, exogenous treatment with the tryptophan metabolite 3-hydroxyanthranilic acid substantially decreased plaque size, 70 whereas pharmacological inhibition or the knockdown of IDO increased arterial inflammation and atherosclerosis. 71,72 Although a controversial study recently suggested a deleterious role for this pathway in atherogenesis, 73 several other data support the notion that IDO-mediated tryptophan metabolism plays an essential role in the maintenance of immune homeostasis in the vascular wall 69 and has beneficial effects on lipoprotein metabolism.…”
Section: Circulation Research February 19 2016mentioning
confidence: 98%
“…68,69 In experimental atherosclerosis, exogenous treatment with the tryptophan metabolite 3-hydroxyanthranilic acid substantially decreased plaque size, 70 whereas pharmacological inhibition or the knockdown of IDO increased arterial inflammation and atherosclerosis. 71,72 Although a controversial study recently suggested a deleterious role for this pathway in atherogenesis, 73 several other data support the notion that IDO-mediated tryptophan metabolism plays an essential role in the maintenance of immune homeostasis in the vascular wall 69 and has beneficial effects on lipoprotein metabolism.…”
Section: Circulation Research February 19 2016mentioning
confidence: 98%
“…IDO1 activity was shown to inhibit IL-10, which, in a model of atherosclerosis, leads to ameliorated disease (Metghalchi et al 2015). Ido1 −/− mice showed blooming of Lactobacilli similar to mice on a tryptophan-rich diet, which resulted in an accumulation of the AhR ligand indole-3-aledhyde.…”
Section: Metabolites As Regulators Of Symbiosismentioning
confidence: 99%
“…The Tampere Vascular Study found that IDO1 expression is elevated in the macrophage‐rich cores of advanced atherosclerotic lesions 25. Levels of Kyn that reflect IDO1 activity are increased in human unstable plaques26 and in rabbit macrophage‐rich atherosclerotic arteries 27. In addition, IDO1 activity in blood significantly and positively correlates with more advanced degrees of atherosclerosis 28.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that epacadostat could help to prevent coronary thrombosis. However, further studies are required, because whether or not IDO1 can prevent atherosclerosis remains controversial 26, 43, 44…”
Section: Discussionmentioning
confidence: 99%